(untitled) (Brazilian Journal of Health Research, 2025)
Introduction: Human immunodeficiency virus (HIV) infection remains a relevant public health issue. While most cases are concentrated in the younger population, the age group above 50 years is on the rise. Objective: To describe the clinical and epidemiological profile of elderly patients infected with HIV/AIDS in the post-HAART era followed at a reference center. Methods: This is an epidemiological, retrospective, qualiquantitative study conducted in the HIV/AIDS outpatient clinic of the Infectious Diseases Service at Cassiano Antônio Moraes University Hospital (Hucam). Results: Of the 60 patients, 60% were male and 40% were female. Self-declared, brown-skinned individuals, with 8-12 years of schooling and heterosexual preference, predominated. The majority (60%) had comorbidities, mainly cardiovascular diseases (37.3%) and endocrinological diseases (18%), with a focus on systemic arterial hypertension, diabetes mellitus, and dyslipidemia. Regarding origin, 65% came from the inpatient ward. Regarding the diagnosis period, 78.3% had a recent diagnosis of HIV/AIDS and 43.3% had opportunistic infections at diagnosis. The median value of CD4 T lymphocytes at the beginning of follow-up was 211.5 cells/µl, being 131 for patients from the inpatient ward and 393 for those from the outpatient clinic. The current CD4 T lymphocyte count was greater than 500 in 36.6% of individuals (71.4% and 17.9% when analyzing the outpatient and inpatient subgroups, respectively). Conclusion: The aging of the HIV/AIDS population with the advent of HAART is a global trend that brings new challenges to health services, requiring comprehensive geriatric assessment and individualized interventions that consider the specificities of the elderly population.